Special Report on Technology Application Design and Development of an Online Repository System for Thesis and Special Problem Manuscripts - Mesa, Armacheska R. (International Journal on Open and Distance e-Learning, 2017)
It is vital to keep track of all the scholarly works undertaken by the students in research universities. As a premier research university,The University of the Philippines (UP) Mindanao has produced several scholarly works made by its students, such as thesis or special problem manuscripts. Similar to typical residential universities in the Philippines, UP Mindanao students submit both hardbound and digital copies of their thesis and special problem manuscripts to their respective departments. Problems such as duplication of work and missing manuscripts are rampant with the current method.This is because printed and electronic copies stored in optical discs can easily be misplaced and are difficult to track when borrowed. This paper describes the development of the UP Mindanao Manuscript e-library and Repository System (UPMERS), which is a web-based information system that provides administrators a tool to monitor and manage records of manuscripts by graduates of the University. This paper also describes the system’s user acceptance using the Technology Acceptance Model (TAM). Furthermore, the study also discusses the result of the System Usability Scale survey.